Intelligence and mental Illness from the perspective of classic and contemporary scholars: Ibn Al-Jawzi as a model - Ali, Asem Shehadeh Saleh; Yeob, Shamsul Jamili (2023)
Psychology, over decades, witnesses tremendous progress, rapid development, and immense contributions in understanding human minds and behavior. The study elucidates Ibn al-Jawzi's views on the concept of intelligence by considering views of Western scholars such as Alfred Binet and others, as well as views of some classic Arab scholars on the same concept. The study adopts descriptive and analytical methodology in analyzing the views of Ibn al-Jawzi in this regard, as well as some similar views of contemporary Western scholars, to prove that Ibn al-Jawzi has valuable views that are consistent with the views of Western scholars in defining intelligence and idiocy. The study concludes that Ibn al-Jawzi had profoundly promoted a vivid concept of intelligence and presented a clear definition of the heart prescribed in the Holy Qur’an which denotes the mind, and obviously, the definition of intelligence is alike to the definition explained by Alfred Binet.